PENINGKATAN PRODUKTIVITAS PERUSAHAAN DENGAN MENGGUNAKAN METODE SIX SIGMA, LEAN DAN KAIZEN - Al Faritsy, Ari Zaqi; Suseno, Suseno (J@ti Undip : Jurnal Teknik Industri, 2015)
Produktivitas merupakan perbandingan antara output dengan input.Jikaoutput yang dihasilkan besar dengan input yang tetap atau lebih kecil dari sebelumnya, maka produktivitas perusahaan mengalami peningkatan. HasilOutput dipengaruhi oleh faktor dalam proses produksi diantaranya defect dan waste. Proses penelitian dengan metodologi six sigma yaitu define, tahap ini mendefinisikan masalah dan aktivitas kerja, selanjutnya measure,tahap ini menghitung waktu baku, menghitung produktivitas awal dan membuat CVSM, kemudian analyze, tahap ini menganalisis penyebab terjadinya waste, dan menganalisis CVSM, dan terakhir improve, tahap ini membuat usulan proses produksi, aktivitas kerja, dan tata letak pabrik untuk meningkatkan produktivitas, menghitung produktivitas baru, dan membuat FVSM. Selain itu juga ada tahap perbaikan dengan 5S. Produktivitas kerja awal rangkaian rangka sebesar 1,56 sigma, setelah dilakukan perbaikan menjadi 1,99 sigma. Pada peta proses operasi saat ini ditemukan waktu transportasi = 37,5 menit dan waktu delay = 305 menit. Pada peta proses operasi usulan dihasilkan waktu transportasi = 16,25 menit dan waktu delay= 70 menit. Pada CVSMwaktu siklus = 4,71 jam, dan lead time = 38,86 jam dengan total WIP = 299 unit. Pada FVSM waktu siklus = 4,399 jam, dan lead time = 30,01 jam dengan total WIP = 198 unit. Â  Â  Abstract Improving productivity is the most important factors in the development of the company to seek profit. Theprocess of improving productiviy can be done by reducing the activity of waste in the production process. Wasteis non-value-added activities in the activity of the production process so that the inefficient use of working time. The purpose of this study is to reduce the activity of waste in the production process to improve productivity. The method used is the six sigma methodology which consists of define, measure, analyse, and improve. Define phase process that defines the problems that occur in the company and work activities. Measurephase process that calculates that standard time, calculate the initial productivity and make the current value stream mapping (CVSM).Analyse phase process is to analyse the causes of waste, and analyse the current value stream mapping (CVSM). Improve phase process that makes the proposed map of the operation, work activities, and plant layout to improve productivity, calculate the new productivity, and create future value stream mapping (FVSM). After that, create a standard operating procedure work culture with 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). The results found early labour productivity series order of 1.56 sigma, after repair to 1.99 sigma. On the map of the current operation discovered the transport time = 37.5 min and a delay time = 305 minutes. On the map of the proposed operation resulting transport time = 16.25 minutes and the time delay = 70 minutes. In CVSM cycle time = 4.71 hours, and lead time = 38.86 hours with a total WIP = 299 units. At FVSM clock cycle time = 4.399, and the lead time = 30.01 hours with a total WIP = 198 units.